2014
DOI: 10.4103/1673-5374.131599
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 promotes the differentiation of hair follicle-derived neural crest stem cells into Schwann cells

Abstract: Hair follicle-derived neural crest stem cells can be induced to differentiate into Schwann cells in vivo and in vitro. However, the underlying regulatory mechanism during cell differentiation remains poorly understood. This study isolated neural crest stem cells from human hair follicles and induced them to differentiate into Schwann cells. Quantitative RT-PCR showed that microRNA (miR)-21 expression was gradually increased during the differentiation of neural crest stem cells into Schwann cells. After transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Therefore, we detected the expression level of mir-21 and SOX-2 three days after osteogenic induction by q-PCR; the result proved our prediction that SOX-2 could be an effective target of mir-21. In addition, recent researches have confirmed our prediction that mir-21 can downregulate SOX-2 protein expression by binding to the 3′-UTR of it [ 41 , 42 ], which may partly explain how mir-21 exerts its biological function in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, we detected the expression level of mir-21 and SOX-2 three days after osteogenic induction by q-PCR; the result proved our prediction that SOX-2 could be an effective target of mir-21. In addition, recent researches have confirmed our prediction that mir-21 can downregulate SOX-2 protein expression by binding to the 3′-UTR of it [ 41 , 42 ], which may partly explain how mir-21 exerts its biological function in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 66%
“…The suppressive effect of miR-21 has been recently seen in other cell types (Trohatou et al, 2014; Ni et al, 2014). Because pluripotency is a critical decision-making step for mESCs, one would expect that several counteracting mechanisms would modulate it so that the mESC pluripotency is maintained in equilibrium with environmental cues.…”
Section: Discussionmentioning
confidence: 87%
“…One of the most significantly regulated miRNAs, miR-21, has been shown to be a direct target of C-JUN in vascular endothelial cells ( Zhou et al., 2011 ), and we found that miR-21-3p is expressed at much lower levels in c-Jun -null injured nerves than in control injured nerves. The function of miR-21 in Schwann cells is unknown, but it has been shown to target Sox2 during differentiation of hair-follicle-derived neural crest stem cells into Schwann cells ( Ni et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%